Tensions In Eu-China Trade Relations: The Impact Of China's Competitive Advantage In Strategic Industries” - Aditya rahman; Sri Sundari (International Journal of Economic Research and Financial Accounting, 2024)
This article reviews trade tensions between the European Union (EU) and China triggered by China's dominance in strategic industries. In the face of an increasingly tense situation, careful policy analysis is needed to proactively manage the complex relationship with China. This research aims to highlight the root causes behind trade conflicts, as well as identify strategies for managing tensions wisely while encouraging mutually beneficial economic cooperation. With a cross-disciplinary approach, this research proposes a framework to reduce the risk of escalation of trade conflicts between the EU and China. Through emphasizing the importance of rigorous policy analysis and innovative solutions, this article highlights the urgency of appropriate policies to maintain domestic economic stability and balanced international relations in the face of challenges from China's economic dominance.